Elastic-plastic stress analysis for an interfacial crack - Ng, Daniel Zhi Jie. (2009)
The plastic zone size at a crack tip is a useful parameter in determining the rate of crack propagation in fracture mechanics. The aim of this work is to determine the size of the plastic zone of an interfacial crack using the distributed dislocation technique and to investigate the influence of stress and other material properties on the plastic zone size. In our analytical investigation of the plastic zone of an interfacial crack, we applied Dugdale’s model for small scale yielding and assumed two small plastic zones at the both crack tips. The crack was modeled as a set of continuous distribution of edge dislocations and the solution was obtained using Erdogan and Gupta’s method and numerical iteration. The plastic zone sizes have been calculated over a range of yield-to-load stresses, shear modulus and Poisson’s ratio for isotropic materials subjected to plane stress. For homogeneous conditions, the plastic zone size is maximum and decreases with increasing non-unity shear modulus ratio and increasing yield-to-load ratio. For materials with same Poisson’s ratio, increasing the Poisson’s ratio would increase the plastic zone size. For materials with different Poisson’s ratio, the maximum plastic zone size remains the same but for a different shear modulus ratio. Graphical results of the influence of yield-to-load stress, shear modulus and Poisson’s ratio on the plastic zone size is also presented.